The Role of Curriculum in Developing Children's Intelligence according to Sayyid Muhammad Qutb: An Islamic Perspective - Hafidzi, Anwar; Ali, Mohd Hatta Mohamed (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to explore the concept of curriculum in developing children's intelligence from the perspective of Sayyid Muhammad Qutb. The study is based on a literature review of Qutb's book "Manhajut Tarbiyah al-Islamiyyah" and other relevant sources. The research found that Qutb's concept of curriculum emphasizes the holistic development of children, including intellectual, emotional, physical, and spiritual intelligence. Qutb believed that all four types of intelligence should be nurtured and developed simultaneously to achieve balanced growth and development in a child. The study also highlights the importance of Islamic values and principles in shaping the curriculum and education system, as they play a crucial role in developing children's character and morality. The research concludes that the implementation of Qutb's concept of curriculum in education can significantly contribute to the development of children's intelligence and character, in line with the principles and values of Islam